Comparative utilization of drone technology vs. traditional methods in open pit stockpile volumetric computation: A case of njuli quarry, Malawi - Matsimbe, Jabulani; Mdolo, Wisdom; Kapachika, Charles; Musonda, Innocent; Dinka, Megersa (Frontiers in Built Environment, 2022)
Despite drones being successfully utilized for monitoring and detecting hazards in mines, there is limited research on their application for open-pit stockpile volumetric computation compared to traditional methods. Furthermore, time, cost, and safety have challenged the use of the traditional approach. Present study aims to fill the gaps by conducting a comparative analysis of stockpile volumetric computation utilizing a drone and traditional approach. A mapping framework is proposed to guide mine personnel on how to conduct open-pit stockpile volumetric computations. The methodology comprises using a drone and traditional survey approach to measure the volume of a known quarry stockpile. Drone-captured images are processed in Pix4D mapper software and geometric techniques are applied to the traditional survey approach. Findings show that the smaller the error of the checkpoints the more accurate the generated model making the measurements re-liable. The generated Pix4D quality report showed a root mean square error of 0.019. The drone percentage error to the actual volume is 2.6% while the traditional approach is 1.3%. Both estimations are less than the maximum allowable percentage error of +/-3 %. Therefore, compared to the traditional approach drone technology provides an accurate, cost-effective, fast, and safe working distance suitable for stockpile volumetric computations in open pit quarries.